2020
DOI: 10.1093/nar/gkaa1033
|View full text |Cite
|
Sign up to set email alerts
|

OncoVar: an integrated database and analysis platform for oncogenic driver variants in cancers

Abstract: The prevalence of neutral mutations in cancer cell population impedes the distinguishing of cancer-causing driver mutations from passenger mutations. To systematically prioritize the oncogenic ability of somatic mutations and cancer genes, we constructed a useful platform, OncoVar (https://oncovar.org/), which employed published bioinformatics algorithms and incorporated known driver events to identify driver mutations and driver genes. We identified 20 162 cancer driver mutations, 814 driver genes and 2360 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 85 publications
0
62
0
Order By: Relevance
“…OncoVar is an integrated database and analysis platform (https://oncovar.org/), by reanalyzing 10,769 exomes from 33 cancer types in TCGA and 1942 genomes from 18 cancer types in International Cancer Genome Consortium (ICGC), it could be used to identify driver mutations and driver genes. 23 Genes were classified into four grades from nonpathogenic to pathogenic: level 0 (non-pathogenic, score = 0), level 1 (possible pathogenic, score = 1), level 2 (likely pathogenic, 1 < score ≤ 10), level 3 (probable pathogenic, 10 < score < 20) and level 4 (pathogenic, score ≥ 20).…”
Section: Oncovar Analysismentioning
confidence: 99%
“…OncoVar is an integrated database and analysis platform (https://oncovar.org/), by reanalyzing 10,769 exomes from 33 cancer types in TCGA and 1942 genomes from 18 cancer types in International Cancer Genome Consortium (ICGC), it could be used to identify driver mutations and driver genes. 23 Genes were classified into four grades from nonpathogenic to pathogenic: level 0 (non-pathogenic, score = 0), level 1 (possible pathogenic, score = 1), level 2 (likely pathogenic, 1 < score ≤ 10), level 3 (probable pathogenic, 10 < score < 20) and level 4 (pathogenic, score ≥ 20).…”
Section: Oncovar Analysismentioning
confidence: 99%
“…RNA-Seq data (GSE147507) for two uninfected human lung biopsies and two lung samples from COVID-19 deceased patient, and RNA-Seq data (CRA002390) for three PBMC samples from healthy donors and COVID-19 patients were analyzed by DESeq2 [16] to identify differentially expressed genes, respectively. Similar to our previous study [17] , false discovery rate (FDR q-value) was calculated by adjusting P -values with the Benjamini-Hochberg method. Genes with FDR q-value < 0.05 and |Log2 (Fold change) | > 1 were considered as DEGs.…”
Section: Identification Of Differential Expressed Genes (Degs)mentioning
confidence: 99%
“…In addition, Wang et al (2021) study constructed a platform, OncoVar, which identified several important drive genes in each cancer type. Immune-related genes were selected and survival analysis was conducted (Supplementary Table 9).…”
Section: External Validationmentioning
confidence: 99%